IMPLEMENTASI NILAI-NILAI ULUL ALBAB DALAM PEMBELAJARAN BAHASA ARAB DI PKPBA UIN MALIKI MALANG: IMPLEMENTATION OF ULUL ALBAB VALUES IN ARABIC LEARNING AT PKPBA UIN MALIKI MALANG - Halimatus Sa'diyah (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract: UIN Maliki Campus Malang aspires to score the people who put forward the dhikr, though, and good deeds. These values ​​are reported to dhikr, fear of Allah, quality of life, earnest and critical, and want to be delivered knowledge. PKPBA is a unit at UIN Malang that is interesting to be used as an initial object that implements the values of Ulul Albab. This type of research is field research, located at UIN Malang. By using qualitative, this research is expected to obtain information from reality, and facts as well as gain a new understanding of the problems of implementing values ​​on the Ulul Albab campus. This research shows that the values ​​of Ulul Albab are developed and developed on this campus, which is evident in the process of learning Arabic at PKPBA. Besides preparing students for Arabic, PKPBA also shapes the personality and character of students in the first year. Values, Arabic learning conducted at PKPBA is loaded with the provisions of Ulul Albab language and values.